The Influence Of Work Motivation, Communication and Workload On Employee Performance at PT. Pegadaian Branch Negara - Windrayuni, I Gusti Ayu Nina Sri; Tabita, I Dewa Ayu Tita Permata; I Gusti Agung Sasih Gayatri (CV. Doki Course and Training, 2025)
Employee performance is certainly considered crucial for a company because employee performance is a key determinant of a company's success. This study aims to determine the influence of work motivation, communication, and workload on employee performance. The research method used in this study is the quantitative method. Quantitative methods are research methodologies that rely on positivism (concrete data), specifically numerical data that will be measured using statistics as a calculation tool. The population and sample used in this study were all employees of PT. Pegadaian Negara Branch. A questionnaire was distributed to 39 respondents. This study employed a saturated sampling method to determine the sample. The data analysis techniques used were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, f-tests, and t-tests using SPSS version 22. The results of this study demonstrate that Work Motivation (X1) partially has a positive and significant effect on Employee Performance at PT Pegadaian Negara Branch. The Communication variable (X2) partially has a positive and significant effect on Employee Performance at PT Pegadaian Negara Branch. The Workload variable (X3) partially has a positive and significant effect on Employee Performance at PT Pegadaian Negara Branch. Based on the results of the F-test analysis, it is shown that the variables Work Motivation (X1), Communication (X2), and Workload (X3) simultaneously have a positive and significant effect on Employee Performance at PT Pegadaian Negara Branch. Recommendations for PT Pegadaian Negara Branch include increasing employee motivation through reward programs and career development, improving internal communication by conducting effective communication training and opening feedback channels, and managing workload more optimally by adjusting task distribution and providing adequate resources.